1997
DOI: 10.1159/000237712
|View full text |Cite
|
Sign up to set email alerts
|

The Activation of the JAK2/STAT5 Pathway Is Commonly Involved in Signaling through the Human IL-5 Receptor

Abstract: The JAK (Janus kinase) family of protein tyrosine kinases and the STATs (signal transducers and activators of transcription) have been shown to be activated in response to a number of cytokines and growth factors. In this study, we evaluated the activation of JAK/STAT pathway upon human interleukin-5 (hIL-5) stimulation of two different hIL-5-responsive cell lines, hIL-5 receptor α-subunit (hIL·5Rα) cDNA-transfected TF-1 (TF-h5Rα) and butyric-acid-treated YY-1 (YY-Bu), and peripheral eosinophils. Immunoprecipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
22
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 7 publications
5
22
0
Order By: Relevance
“…Given this background, together with the observation that STAT proteins are important substrates for JAKs, we tested the hypothesis that STAT proteins are involved in the signaling events controlling gene expression in eosinophils. We and others have observed that the transcription factors STAT1 (14,15) and STAT5 (16,17) are expressed and activated in human eosinophils; however, there are no reports of the expression of STAT3 nor which STAT5 isoform(s), STAT5a and/or STAT5b, is expressed in these cells. Recent studies have confirmed that the mRNA for all three isoforms is abundant in human peripheral blood eosinophils (18).…”
Section: Expression Of Stat3 Stat5a and Stat5b In Human Eosinophilsmentioning
confidence: 88%
See 1 more Smart Citation
“…Given this background, together with the observation that STAT proteins are important substrates for JAKs, we tested the hypothesis that STAT proteins are involved in the signaling events controlling gene expression in eosinophils. We and others have observed that the transcription factors STAT1 (14,15) and STAT5 (16,17) are expressed and activated in human eosinophils; however, there are no reports of the expression of STAT3 nor which STAT5 isoform(s), STAT5a and/or STAT5b, is expressed in these cells. Recent studies have confirmed that the mRNA for all three isoforms is abundant in human peripheral blood eosinophils (18).…”
Section: Expression Of Stat3 Stat5a and Stat5b In Human Eosinophilsmentioning
confidence: 88%
“…We, and others, have previously reported that STAT5 from IL-5-or GM-CSF-treated human eosinophils can bind DNA (16,17), but it is unknown which STAT5 isoform, or whether both, bind to the STAT consensus DNA site. Therefore, we conducted EMSAs in which we included Abs specific for STAT5a or STATb that do not cross-react with the other isoforms and that are known to perform in Ab supershift experiments (22).…”
Section: Dna-binding Activity Of Protein From Il-5-or Gm-csf-treated mentioning
confidence: 96%
“…mined. It is likely that CrkL phosphorylation by the IL-5R is regulated by receptor-associated JAK kinases, notably JAK1 and/or JAK2 (30,33,36,39,42,45,79), although it is possible that Lyn, which is also associated with the ␤ subunit of the receptor (32,37,41,47), may mediate such tyrosine phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Since neither subunit of IL-5R possesses inherent tyrosine kinase activity, its phosphorylation requires receptor-associated tyrosine kinases, including Lyn, JAK1, and JAK2 (33,34,37,41). Stimulation of eosinophils with IL-5 rapidly induces the phosphorylation and activation of JAK1, JAK2, and Lyn (34,37), which then phosphorylate both the ␣ and ␤ c subunits of the IL-5R, resulting in the recruitment and activation of Shc, Grb2, SHP-2, and the STAT proteins, primarily STAT1 and STAT5 (36,42,43). The Janus kinases serve to couple these STAT proteins to IL-5R activation.…”
mentioning
confidence: 99%
See 1 more Smart Citation